DNP student mentorship: Empowering students and nurse practitioner organizations. Issue 4 (April 2020) - Higgins, Karen; Newby, Olivia
Abstract : Abstract: NP organizations can complement academic programs by providing DNP students with experiential learning and mentorship. This article focuses on a regional NP organization that provided mentoring to DNP students who joined their leadership board. Students gained leadership, advocacy, policy, and advanced practice experience, and the organization experienced growth and innovation. Abstract : NP organizations can complement academic programs by providing DNP students with experiential learning and mentorship. This article focuses on a regional NP organization that provided mentoring to DNP students who joined their leadership board. Students gained leadership, advocacy, policy, and advanced practice experience, and the organization experienced growth and innovation.